5 - A Demand-driven Model of Decentralised Land-use Planning and Natural Resource Management: Experiences from the Chiredzi District of Zimbabwe - Mandondo, Alois; Kozanayi, Witness (Africa Development, 2006)
Decentralisation should ideally result in the transfer of effective power and control from the state to elected local level authorities – it should take a democratic form. But most decentralisation reforms turn out to be supply-led interventions in which states and other upper level actors, most of whom have a predilection to retain far-reaching control, define the form and extent of powers to be given to local-level authorities, usually resulting in de-concentration. This paper uses empirical evidence from Zimbabwe to argue that decentralisation is likely to result in more thoroughgoing empowerment if it is demand-driven. Even if empowerment is demanded we note that relations in decentralised arenas are not necessarily always egalitarian. We therefore argue that efforts to resolve the dilemma of community marginalisation through decentralisation should not lose sight of local level equity dimensions. We caution that demand-driven decentralisation should not be misconstrued as implying that the state and other external actors should completely retire from the business of the local. Effective empowerment appears to require a preserved role for upper level (non-local) actors, especially in providing political legitimation, technical backstopping, financial support and resolving issues whose solutions transcend the scope and scale of the local.